2014
DOI: 10.1007/s12031-014-0338-z
|View full text |Cite
|
Sign up to set email alerts
|

PACAP Stimulates Functional Recovery after Spinal Cord Injury through Axonal Regeneration

Abstract: Pituitary adenylate cyclase-activating polypeptide (PACAP) is a neuroprotective peptide expressed in the central nervous system. Although many studies have shown a neuroprotective effect of PACAP, the mechanism of PACAP in the treatment of spinal cord injury (SCI) is yet to be elucidated. The purpose of this study was to examine the efficacy and underlying mechanism of PACAP in a mouse SCI model where PACAP was delivered via a biodegradable hydrogel. When PACAP or saline was delivered immediately after SCI, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…It has been demonstrated that PACAP can prevent the harmful effect of oxidative stress [ 16 , 17 ], trigger the activation of anti-inflammatory processes and can have a positive role during ischemic conditions [ 18 ]. PACAP is also known to activate the immune system [ 19 ] and to induce tissue regeneration [ 20 ]. It plays an important role in the development of different organs, regulates chondrogenesis and spermatogenesis [ 16 ], and influences the development of the central nervous system [ 10 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that PACAP can prevent the harmful effect of oxidative stress [ 16 , 17 ], trigger the activation of anti-inflammatory processes and can have a positive role during ischemic conditions [ 18 ]. PACAP is also known to activate the immune system [ 19 ] and to induce tissue regeneration [ 20 ]. It plays an important role in the development of different organs, regulates chondrogenesis and spermatogenesis [ 16 ], and influences the development of the central nervous system [ 10 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the well-established and most intensively studied actions are PACAP’s neurotrophic and neuroprotective effects. PACAP has been shown to protect neurons against various noxious stimuli in vitro and in vivo [6,7,8] For example, PACAP is protective in traumatic brain [9] and spinal cord injury [10], in global and focal cerebral ischemia [6], in models of Huntington’s disease [11], and in Parkinson’s disease [12,13,14]. …”
Section: Introductionmentioning
confidence: 99%
“…PACAP exerts multiple functions through three specific receptors - PACAP receptor 1 (PAC1R) and two VIP/PACAP receptors [ 13 , 14 ]. Exogenous and endogenous PACAP decreases neuronal cell death after ischemia, SCI, and other neuronal disorders [ 15 - 20 ]. PACAP also contributes to suppress inflammatory/immune responses.…”
Section: Introductionmentioning
confidence: 99%